Cancer vaccine adjuvants – recent clinical progress and future perspectives. (February 2015) - Banday, Abid H.; Jeelani, Salika; Hruby, Victor J.
Abstract Despite recent breakthroughs in the prognosis, prevention and treatment, cancer still remains the leading cause of death and affects millions of people worldwide. With the US FDA approval of various preventive cancer vaccines such as Gardasil (Merck), Cervarix (Glaxosmithkline) and the therapeutic vaccine Sipulencel-T (Provenge), cancer vaccine development is gaining huge ground. Approval of these vaccines has encouraged the concept of cancer treatment through cellular immunotherapy. The FDA approval of the above vaccines has provided support for renewed interest and attention which the development of new therapeutic cancer vaccines deserves. However, most of the new generation vaccines including that for cancer are poorly immunogenic sub-unit vaccines and thus essentially need adjuvants in their formulations to compensate for the immune suppression. Adjuvants are the essential components of a potent vaccine which increases the efficacy by enhancing the antigen-specific immune response. However, the design of a successful adjuvant is not easy because of the complexity and the difficulty in designing adjuvants that are safe, potent and economically viable. The present communication takes a short review of the advancements in adjuvant technology, current clinical scenario of new adjuvants and application of their molecularly defined formulations to new generation cancer vaccines which are currently under development.